Identifying Soil Erosion-Prone Areas in the Wadi Haly Catchment, Saudi Arabia Using Morphometric Analysis and Watershed Features - Bashar Bashir; Abdullah Alsalman (Applied Sciences)
Soil erosion has several significant impacts on human and environmental activities that make it an important topic with significant worldwide ramifications. Analyzing morphometric indices provides essential insights into watershed geomorphology, which is key to forecasting and assessing diverse natural hazard dynamics. To ensure effective and sustainable watershed management and resource distribution, it is essential to identify critical catchments or prioritize sub-catchments. In this study, morphometric analysis and prioritization were applied to 15 sub-catchments within the Wadi Haly catchment to identify the one most susceptible to soil erosion. This research focuses on the analysis of 15 sub-catchments within the Wadi Haly catchment in Saudi Arabia, utilizing GIS tools alongside various parameters to guide both short- and long-term catchment management. A combined parameter, developed from several morphometric indices for each sub-catchment, was used to classify the Wadi Haly catchment into three levels of soil erosion risk. The results show that sub-catchments 1, 7, 11, 12, and 13, with areas of 694.1 km2, 517.87 km2, 677.99 km2, 200.39 km2, and 326.55 km2, respectively, are contributing significantly to erosion in the region. In contrast, sub-catchments 3, 8, 9, 10, and 15 exhibit minimal erosion impact. To mitigate severe erosion, strategies such as contour farming, terracing, the use of filter strikes, as well as various structural or non-structural interventions could be applied.